2018
DOI: 10.1007/s40123-017-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Scleral Metastasis of Esophageal Squamous Cell Carcinoma

Abstract: In this report, a case of ocular scleral metastasis was reported in a patient with a past history of esophageal squamous cell carcinoma. The patient was a 58-year-old male who was admitted to Urmia Imam Khomeini Hospital, Urmia, Iran, 8 years ago with progressive dysphasia. Seven years after initial diagnosis and treatment of esophageal cancer, the patient had no signs or symptoms of the disease. But 2 months ago, he was referred to the hospital due to ocular swelling, redness and watering. Pathologic examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that the 2-year survival rate was 1.3 and 27%. Another more recent study showed a mean survival of 7.4 months after the discovery of oculoorbital metastasis regardless of the histological type of the primary tumor [8].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies have shown that the 2-year survival rate was 1.3 and 27%. Another more recent study showed a mean survival of 7.4 months after the discovery of oculoorbital metastasis regardless of the histological type of the primary tumor [8].…”
mentioning
confidence: 96%
“…Case Reports in Ophthalmological Medicine Sclerotic involvement is an extremely rare form and may be revealed by a scleral nodule that may simulate anterior nodular scleritis, decreased visual acuity, ocular redness, eye pain, or watery eyes [8].…”
mentioning
confidence: 99%